Substantial injuries influence ranking position in young elite athletes of athletics, cross-country skiing, orienteering - von Rosen, P.; Heijne, A. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The relationship between injury and performance in young athletes is scarcely studied. The aim of this study was therefore to explore the association between injury prevalence and ranking position among adolescent elite athletes. 162 male and female adolescent elite athletes (age range 15-19), competing in athletics (n=59), cross-country skiing (n=66) and orienteering (n=37), were monitored weekly over 22-47 weeks using a web-based injury questionnaire. Ranking lists were collected. A significant (p=.003) difference was found in the seasonal substantial injury prevalence across the ranked athletes over the season, where the top-ranked (median 3.6%, 25-75thpercentiles 0-14.3%) and middle-ranked athletes (median 2.3%, 25-75thpercentiles 0-10.0%) had a lower substantial injury prevalence compared to the low-ranked athletes (median 11.3%, 25-75thpercentiles 2.5-27.1%), during both pre-season (p=.002) and competitive season (p=.031). Athletes that improved their ranking position (51%, n=51) reported a lower substantial injury prevalence (median 0%, 25-75thpercentiles 0-10.0%) compared to those that decreased (49%, n=49) their ranking position (md 6.7%, 25-75thpercentiles 0-22.5%). In the top-ranked group, no athlete reported substantial injury more than40% of all data collection time points compared to 9.6% (n=5) in the middle-ranked and 17.3% (n=9) in the low-ranked group. Our results provide supporting evidence that substantial injuries, such as acute and overuse injuries leading to moderate or severe reductions in training or sports performance, influence ranking position in adolescent elite athletes. The findings are crucial to stakeholders involved in adolescent elite sports and support the value of designing effective preventive interventions for substantial injuries.